Completion and monitoring of the geomorphic-based LIFE RIBERMINE project: transference to other abandoned mines - Martín Duque, J.F.; Tejedor, M.; Royal, P.; Martín-Moreno, C.; Hancock, G.R.; de la Villa, J.; Solórzano, M.A. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
At the 2022 Mine Closure Conference, we presented the ongoing geomorphic rehabilitation, landscape evolution modelling and geochemical stabilisation works for the LIFE RIBERMINE project at Peñalén (Spain) and Lousal (Portugal). Two years later, we describe the completion of the project at the Spanish location, focusing on finishing of the geomorphic regrading, by imprinting ‘mature’ catchments (using GeoFluv – Natural Regrade) at the former waste dumps and in ‘sculpting’ strikingly ‘natural’ limestone cliffs at a sector of the mine highwall (using the Talus Royal method). The total area subject to geomorphic regrading has been of 13.05 ha, from which 11.06 ha are fluvial geomorphic rehabilitation and 1.99 ha of hard rock geomorphic landforming. The total earth movement has approached 250,000 m3. The complete and correct construction of the Talus Royal has been the main novelty from 2022 to 2024 and has been a clear success, since we were able to accurately build the design, demonstrating that it is a feasible technique to be included in mine closure plans. The project monitoring has been broad and diverse. We focus on measuring soil erosion in the field with temporary check dams since sediment spill was the main environmental problem to solve at the Spanish site. From a pre-rehabilitation sediment yield of 353 t ha−1 yr−1, we have measured, for the post-rehabilitation scenario: external west waste rock dump (WRD) (7.4 t ha−1 yr−1) external east WRD (3.1 t ha−1 yr−1) in-pit backfilling (7 t ha−1 yr−1). SIBERIA modelling at such sites predicted results very close to these values. The effective results of LIFE RIBERMINE have allowed the transference of such geomorphic-based solutions to about 80 ha of new rehabilitation projects of abandoned mines in Spain, already completed. Two of them resulted from the recovery and use of bond guarantees by regional administrations, four projects funded by the European Union (EU) Recovery, Transformation and Resilience Plan (Next Generation EU funding), two sites for a mine company in Spain (SAMCA), and even one example in civil works. LIFE RIBERMINE has also been a training site for companies from Sweden (LKAB) and Colombia (Carbones del Cerrejón Limited, Glencore).